EFEKTIVITAS PEMBINAAN NARAPIDANA ANAK Di LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) PEKANBARU - Eric lambue Tampubolon; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The increasing criminal cases commited by children led to a growing importance the role of coaching. The coaching was carried out in Child Correctional Institution (LPKA Pekanbaru). The purpose of the coaching is to make the child prisoners not to repeat a criminal act.The purpose of this research is to find out the effectiveness of the coaching of child prisoners in Pekanbaru Child Correctional Institution and the factors affecting the effectiveness of the coaching in Pekanbaru Child Correctional Institution (LPKA Pekanbaru). This research uses the concept of the theory of effectiveness by Mahmudi. This research used a qualitative approach, method to collect data through interview, observation and documentation.Based on the result of the research through interviews and observations, it is known that the coaching of child prisoners in Pekanbaru Child Correctional Institution (LPKA Pekanbaru) has been effective. Coaching is effective because the purpose has been reached. The result analysis showed in which the factors that affect the effectiveness of coaching of this program are:facilities and infrastructure, human resources, the psychological of children and child discipline.Keywords : Effectiveness, Child Prisoners, Coaching